Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702425
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Users' Touch Behavior on Large Mobile Touch-Screens and Assisted Targeting by Tilting Gesture

Abstract: As large-screen smartphones are trending, they bring a new set of challenges such as acquiring unreachable screen targets using one hand. To understand users' touch behavior on large mobile touchscreens, we conducted an empirical experiment to discover their usage patterns of tilting devices toward their thumbs to touch screen regions. Exploiting this natural tilting behavior, we designed three novel mobile interaction techniques: TiltSlide, TiltReduction, and TiltCursor. We conducted a controlled experiment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
0
29
1
1
Order By: Relevance
“…Rekimoto [25] and Weberg et al [36] explored using a tilt signal to navigate menus and 2D maps. Several other studies [8,12,33] also explored single-handed interaction on mobile devices by combining motion and touch to 1) assist targeting and extend thumb's reach [8], 2) enhance navigation with quick command gestures [33], and 3) enable new types of motion gestures, such as tilt to zoom, pivot-to-lock, and shake to delete [12]. Although there have been many attempts to use tilt and tilt gestures for text entry, we have applied tilt to shape writing to address the single-handed text entry problem.…”
Section: Tilt-based Mobile Interaction and Text Entrymentioning
confidence: 94%
“…Rekimoto [25] and Weberg et al [36] explored using a tilt signal to navigate menus and 2D maps. Several other studies [8,12,33] also explored single-handed interaction on mobile devices by combining motion and touch to 1) assist targeting and extend thumb's reach [8], 2) enhance navigation with quick command gestures [33], and 3) enable new types of motion gestures, such as tilt to zoom, pivot-to-lock, and shake to delete [12]. Although there have been many attempts to use tilt and tilt gestures for text entry, we have applied tilt to shape writing to address the single-handed text entry problem.…”
Section: Tilt-based Mobile Interaction and Text Entrymentioning
confidence: 94%
“…Some researchers have explored how to use grasp and orientation information to enrich the interaction, e.g. help selecting an action item on the device through pointing [6,7,11] or changing the orientation of the phone to landscape [4]. However these works only focus on specific applications or hardware implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research into transitions or movements have focussed on the constraints of using a single-handed grip to interact with the device by tilting it to bring it into range of the thumb [6,7,10]. These works focus on a single device type and single device size.…”
Section: Pre-touch Sensing For Mobile Interactionmentioning
confidence: 99%
“…In testing of Hypotheses H1, H3 and H5, the second quantitative study also showed that participants, made similar twists along the Beta and Gamma axes for Target Positions 1, 2, 3 and 4 (see Figures 11 and 13). The adaptive homepage concept has some similarities with "tilt slide" [10]. In this concept homepage icons shift closer to the dominant hand when tilt is sensed along both the Beta and Gamma axes ( Figure 17).…”
Section: Adaptive Homepagementioning
confidence: 99%
See 1 more Smart Citation